Fatores intrínsecos do custo energético da locomoção durante a natação - Caputo, Fabrizio [UNESP]; De Oliveira, Mariana Fernandes Mendes [UNESP]; Denadai, Benedito Sérgio [UNESP]; Greco, Camila Coelho [UNESP] (FapUNIFESP (SciELO), 2006)
The amount of metabolic energy spent in transporting the body mass of the subject over a unit of distance has been defined as the energy cost of locomotion, or regarding to swimming, cost of swimming. The differences in the cost of swimming between the individuals seem to be influenced by two main factors, the hydrodynamic resistance and technical skill of the swimmer. The lower cost of swimming showed by females has been attributed to a smaller hydrodynamic resistance due to their smaller size, larger percentage fat and more streamlined position. However, the difference in cost of swimming between males and females disappears when correcting for body size. With regard to children, the higher energy cost of swimming when correcting for body size may be caused by the lower swimming technique showed by them. For individuals with the same anthropometric characteristics, the better swimming technique and larger size of propelling surface, associated with higher propelling efficiency, may decrease the energy cost of swimming. When comparing different types of strokes, the most economical stroke is crawl, followed by backstroke, irrespective the swimming velocity. Butterfly is the less economical at low velocities (< 0.8 m·s-1). However, above that velocity the breaststroke become the less economical stroke.
Intrinsic factors of the locomotion energy cost during swimming
Keywords: Children; Cost of swimming; Gender; Swimming strokes